2019
DOI: 10.1038/s41586-019-1865-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial bile acid metabolites modulate gut RORγ+ regulatory T cell homeostasis

Abstract: The metabolic pathways encoded by the human gut microbiome constantly interact with host gene products through numerous bioactive molecules 1. Primary bile acids (BAs) are synthesized within hepatocytes and released into the duodenum to facilitate absorption of lipids or fat-soluble vitamins 2. Some BAs (~5%) escape into the colon, where gut commensal bacteria convert them into a variety of intestinal BAs 2 that are important hormones regulating host cholesterol metabolism and energy balance via several nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
521
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 695 publications
(581 citation statements)
references
References 34 publications
15
521
3
Order By: Relevance
“…The effect of isoDCA on dendritic cells in this study is in contrast to recent work of T‐cell‐modulating bile acids, which potentiate Treg generation in a cell‐intrinsic manner 5,6 . This suggests that bile acids have diverse effects on the adaptive immune system and affect multiple cell types, opening the door for further research on how microbial metabolites can influence immune responses.…”
Section: Figurecontrasting
confidence: 76%
See 2 more Smart Citations
“…The effect of isoDCA on dendritic cells in this study is in contrast to recent work of T‐cell‐modulating bile acids, which potentiate Treg generation in a cell‐intrinsic manner 5,6 . This suggests that bile acids have diverse effects on the adaptive immune system and affect multiple cell types, opening the door for further research on how microbial metabolites can influence immune responses.…”
Section: Figurecontrasting
confidence: 76%
“…The molecular mechanism by which the microbiome interacts with peripherally induced Treg (pTreg) is likely complex and multifactorial; however, part of the effect is mediated via the release of microbial fermentation products, such as butyrate and other short‐chain fatty acids 1–3 . In a string of recent studies, a role for host bile acids has also been shown to induce pTreg generation, with this function dependent on commensal colonization 4–6 . In the recent issue of Nature , Rudensky and colleagues dissect the molecular fermentation pathway where the gut microbiome converts an endogenous bile acid into an immunologically active bile acid with the capacity to induce pTreg in the gut 4 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…One of these diseases is ulcerative colitis, an inflammatory bowel disease. Ketogenic diets may dampen inflammation within the gastrointestinal tract by inhibiting the activity of the NLRP3 inflammasome (8), promoting intestinal stem cell regeneration and gut healing (9), and stimulating the release of bile acids that facilitate intestinal immune system homeostasis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…These effects have been attributed to inhibition of the inflammatory unfolded protein response [60]. Additionally, it was recently found that depletion of gut microbial bile acids leads to reduced gut RORγ+ regulatory T cells via a mechanism involving bile acid activity at the vitamin D receptor [61], though it is not clear if this has an effect on distant organs such as the lung.…”
Section: Bile Acidsmentioning
confidence: 99%